Innovation and entrepreneurship : a competency framework - Matthews, Charles H. (Economist); Brueggemann, Ralph (Routledge, 2015)
This book presents a new model, the competency framework, for students, innovators, entrepreneurs, managers, and anyone who wants to better understand the dynamic world of innovation and entrepreneurship. Focused on both the individual and strategic organizational level, this book is about people and the competencies each person needs to learn to be successful in creating a more dynamic future. Matthews and Brueggemann's framework for innovation and entrepreneurship competencies empowers individuals to excel at innovation and new venture creation. It provides a practical guide and clear and co.
Keywords: management inovací; inovační podnikání; tvůrčí myšlení; innovation management; innovative business; creative thinking; příručky; elektronické knihy; handbooks and manuals; electronic books